Morphology and bionomics of Ac.F.R.86 (Hymenoptera; Ichneumonidae) with special reference to reproduction and sex ratio - Van Heerden, H. P.(Hendrik Petrus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1945.